Effects of Flow Parameters on the Characteristics of Biogas Flames in a Crossflow Air Stream - Harish, A.; Raghavan, V. (Engineering Science & Technology, 2022)
This study presents the flame characteristics of laminar cross-flow non-premixed biogas-air flames established in a boundary layer using ANSYS Fluent. The validated numerical model incorporates variable thermo-physical properties, multi-component diffusion, short chemical kinetics mechanism, and optically thin approximation-based radiation model. Fuel is injected at a uniform velocity and the air is supplied perpendicular to it. Predicted and the in-house experimental biogas flames are qualitatively compared in terms of flame extents. The fuel flow rate is varied from 0.02 m/s to 0.04 m/s to study the effects of power rating on the flame characteristics. At a given fuel flow rate, the airflow rate is incremented in steps to examine the effects of forced convection on the characteristics and stability of the flames. Furthermore, the effects of the upstream flat plate length, ahead of the fuel injector’s leading edge, on the flame anchoring location have been studied. The structure and characteristics of the reactive boundary layer are explained using fields of temperature, velocity, mass fractions of major species, stoichiometric equivalence ratio, and Damköhler number. The reactive boundary layer fueled by methane is compared with that of biogas.